2022
DOI: 10.1039/d2cp01200f
|View full text |Cite
|
Sign up to set email alerts
|

Self-aggregation, H-bonding, and photoresponse in film and solution states of azobenzene containing polyurea

Abstract: We critically understand the hydrogen bonding interactions and electronic transitions occurring in a thin film as well as in solution of a photo-responsive polymer, azo-polyurea (azo-PU). We synthesize azo-PU by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Although the isomer stability of azobenzene in the polymer is primarily determined by the polarity of dipole moment in the trans - and cis -forms, other factors including van der Waals force, hydrogen bonding, molecular weight, alignment of polymer, and steric hindrance are also known to have an effect. For instance, previous research on an azobenzene-based organic semiconductor polymer demonstrated that an equilibrium state of the film (condensed phase) comprises a combination of trans - and cis -forms due to steric hindrance in contrast to the dispersion in solution (liquid phase).…”
Section: Resultsmentioning
confidence: 99%
“…Although the isomer stability of azobenzene in the polymer is primarily determined by the polarity of dipole moment in the trans - and cis -forms, other factors including van der Waals force, hydrogen bonding, molecular weight, alignment of polymer, and steric hindrance are also known to have an effect. For instance, previous research on an azobenzene-based organic semiconductor polymer demonstrated that an equilibrium state of the film (condensed phase) comprises a combination of trans - and cis -forms due to steric hindrance in contrast to the dispersion in solution (liquid phase).…”
Section: Resultsmentioning
confidence: 99%
“…One can further utilize this study for evaluating the molecules to increase the interfacial charge dynamics, stability, efficiency and lifetime of perovskite materials [226,227,228]. This study can be extended to understand the influence of solvent or intermolecular interactions [229,230] on the charge migration dynamics and the nonlinear optical properties such as high harmonic spectra [231]. Hence, we hope our results will encourage and inspire further research in the direction of molecular modelling.…”
Section: Discussionmentioning
confidence: 79%
“…A tanulmány segítségével értékelhetők a molekulák annak érdekében, hogy növeljük a perovszkit anyagok határfelületi töltésdinamikáját, stabilitását, hatásfokát és élettartamát [226,227,228]. A dolgozat tovább bővíthető, hogy megértsük a különböző közegek vagy molekulák közötti kölcsönhatások hatását a töltésmigrációs dinamikára [229,230] és olyan nemlineáris optikai tulajdonságokra, mint a magasharmonikus-keltés spektruma. [231] Reméljük, hogy az eredményeink további kutatásokra ösztönöznek és újabb utakat nyitnak a molekulamodellezés irányában.…”
Section: Magyar Nyelvű öSszefoglalóunclassified